Your nose is as sleek as goose fat: the standard of Chinese beauty in the English tongue - Wang, Hui; Looi, Wai Ling (Penerbit Universiti Kebangsaan Malaysia, 2021)
In Hong Lou Meng, the straightforward description of the appearances of young women characters is highly prevalent; Cao used rhetorical devices of metaphors and similes to present abstract beauty into something visual. As English and Chinese culture and the norms of works of literature do not share the same standard of beauty and the choice of images, the translation, on one hand, runs into the dilemma of keeping the image of the original and thus compromises its reader’s understanding; yet on the other hand, abandoning the image of the original loses the image of beauty depicted in the source text. This paper concentrates on translation into English of the metaphors utilised in describing the beauty of females in Hong Lou Meng, by Yang Xianyi and Gladys Yang (1978) and by David Hawkes and John Minford (1973). Linguistic metaphors are categorised based on Dagut’s (1976) notion of shared cultural experiences and semantic association whilst the main aim is to find out the extent to which the original image could be retained. The findings show that retention of images in translating beauty-related metaphors is acceptable in shared metaphors and half-shared metaphors. As for non-shared metaphors, the retention of images is acceptable with some additional ‘help’ by adding sense. Meanwhile, the usage of standard TL image, be it added with sense or made more explicit through the usage of simile, should be avoided as far as possible in canonised texts.